Discovery of potent inhibitors for Mpro enzyme of SARS-COV2 by multi-stage in-silico screening of Alkannin/shikonin. Issue 18 (8th September 2022) - Kumar, Nitish; Singh, Jatinder Vir; Bhagat, Kavita; Gulati, Harmandeep Kaur; Sharma, Anchal; Rani, Archana; Duggal, Amit; Gulati, Puja; Singh, Harbinder; Bedi, Preet Mohinder Singh; Kaur, Sarabjit
Abstract: Novel coronavirus disease, a serious challenge for the healthcare system, has diverted all the researchers toward the exploration of potential targets, compounds or vaccines for the management of this disease. M pro enzyme was found to be crucial for replication of this virus which makes this enzyme an attractive drug target for SARS-CoV-2. Diverse pharmacological profile of Alkannin/shikonin (A/S) derivatives build up curiosity to study their antiviral profile. Therefore, current study utilises various computational tools to screen and evaluate all the discovered A/S derivatives to inhibit the M pro enzyme for its anti-viral activity. Results revealed that the A/S has a very good tendency to inhibit the catalytic activity of the enzyme. Moreover, (5 R, 6R)-5, 8-dihydroxy-6-methoxy-3, 4, 5, 6-tetrahydro-2H-benzo[a]anthracene-1, 7, 12-trione, an A/S derivative was found to possess drug-likeliness properties and a good ADME profile. Moreover, its complex with Mpro enzyme was found stable for 50 ns which makes it a very promising ligand to treat COVID-19. Graphical Abstract: UF0001